PERAN PROFESIONALISME GURU PAI DALAM PENGUATAN PROFIL PELAJAR PANCASILA DI SD TUNAS HARAPAN KABUPATEN TANGERANG - Ana Safitri; Hidayatullah Hidayatullah; Fitri Hilmiyati; Wasehudin Wasehudin; Mufti Ali; Fandy Adpen Lazzavietamsi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The Pancasila student profile is one of the demands in the Independent Curriculum. The professionalism of PAI teachers plays a role in encouraging students to have Pancasila values within themselves. The aim of the study aims to analyze the role of PAI teacher professionalism in increasing the profile of Pancasila students. This study is qualitative research using a case study method at SD Tunas Harapan Pasar Kemis, Tangerang Regency. Data was collected through interview techniques, documentation studies and observations. After that, the data was collected, reduced, presented and concluded. The competency of PAI teachers at Tunas Harapan Elementary School shows that it is in accordance with the standards mandated by the 2003 National Education System Law. The roles of professional teachers that PAI teachers can play include, among others, uswatun hasanah, motivator, facilitator and evaluator. There are several efforts to improve the professionalism of PAI teachers to strengthen the profile of Pancasila students, including taking part in Diktats, Workshops, Webinars and playing a role in PAI subject clusters. Even as a professional teacher, there are obstacles and obstacles that we face, such as unsynchronized time, difficulties in determining dimensions and elements related to PAI teaching materials.